A cross-cultural comparison of East and Western academic literature on adventure tourism. (December 2018) - Cheng, Mingming
In the past two decades, adventure tourism enjoyed great popularity in China with rapid growth of participants. Parallel to this is an increasing number of research publications on Chinese adventure tourism, which cover similar topics to that of Western adventure tourism literature but are largely based on a Chinese perspective. In order to bridge the Western and Chinese academic literature on adventure tourism, a text-driven review approach is utilized to analyze both sources of literature to identify their similarities and differences. The results reveal that while Chinese adventure tourism scholars seek knowledge from the Western world, Chinese adventure tourism has its own dynamics, which include their organization models and Chinese tourists' aesthetic way of approaching adventure tourism experiences. By developing deeper knowledge on how adventure tourism operates in China, alternative interpretations that Chinese tourists offer, and the divergence of views in adventure tourism, the study reflects the need for a grounded approach, which will help penetrate the invisible academic wall.